Acceptability of self-conducted home-based HIV testing among men who have sex with men in Brazil: data from an on-line survey - Sheri A. Lippman; André R. S. Périssé; Valdiléa G. Veloso; Patrick S. Sullivan; Susan Buchbinder; R. Craig Sineath; Beatriz Grinsztejn (Cadernos de Saúde Pública, 2014)
The Brazilian HIV/AIDS epidemic is concentrated among men who have sex with men (MSM), however HIV testing rates among MSM are not commensurate with their risk. Strategies to expand early diagnosis may include use of self-conducted home-based testing kits, which are now available for purchase in the US. In April 2011 we conducted a survey with Brazilian MSM using Facebook to assess HIV testing preferences and acceptability of home-based testing. Among 356 previously tested, HIV-negative MSM, 47% reported a preference for home-based testing, 27% preferred clinic-based testing, and 26% had no preference. Less frequent testers and those who had considered testing but failed to test were more likely to prefer home-based testing. Close to 90% reported that they would use self-test kits; 62% and 54% said they would use home-based testing to make choices about unprotected sex with regular and new partners, respectively. Concerns included difficulty to understand the tests (32%) and receiving results alone (23%). Overall, home-based testing may appeal to MSM and result in increased testing frequency. Research on feasibility and utilization of self-tests in practice is needed.